The efficacy of lapatinib in metastatic breast cancer with HER2 non-amplified primary tumors and EGFR positive circulating tumor cells: a proof-of-concept study. - Justin Stebbing; Rachel Payne; Justine Reise; Adam E Frampton; Miranda Avery; Laura Woodley; Angelo Di Leo; Marta Pestrin; Jonathan Krell; R Charles Coombes (PLoS ONE, 2013)
Background Analysis of circulating tumor cells (CTCs) provides real-time measures of cancer sub-populations with potential for CTC-directed therapeutics. We examined whether lapatinib which binds both HER2 and EGFR could induce depletion of the EGFR-positive pool of CTCs, which may in turn lead to clinical benefits. Patients and methods Patients with metastatic breast cancer and HER2 non-amplified primary tumors with EGFR-positive CTCs were recruited and lapatinib 1500 mg daily was administered, in a standard two step phase 2 trial. Results There were no responses leading to termination at the first analysis with 16 patients recruited out of 43 screened. In 6 out of 14 (43%) individuals eligible for the efficacy analysis, a decrease in CTCs was observed with most of these having a greater decrease in their EGFR-positive CTC pool. Conclusions This is one of the first studies of CTC-directed therapeutics and suggests that lapatinib monotherapy is not having any demonstrable clinical effects by reducing the EGFR-positive pool of CTCs in HER2 non-amplified primary tumors. Our attempt to expand the pool of patients eligible for a targeted therapy was unsuccessful; the role of clonal populations in cancer biology and therapeutic strategies to control them will require extensive evaluation in years to come. Trial registration Clinical trials.gov NCT00820924.